Evaluation of the Effifacy of a Phage Cocktail against gentamicin-resistance Klebsiella pneumoniae - Paran, Andrea Ken; Mamora, Dewi; Fong, Gemma Kah Yi; Lihan, Samuel; Zulkarnain, Azham; Tan, Cheng Siang (UMT, 2020)
The bacteria Klebsiella pneumoniae is one of top aetiological agents associated with nosocomial infection, and it has gained its notoriety with the emergence of multidrug resistance strains. In this study, we evaluated the effect of lytic bacteriophage cocktail isolated from our local sewage as potential antimicrobial candidate against Gentamicinresistant Klebsiella pneumoniae. A total of five clinical-acquired K. pneumoniae isolates including a carbapenem-resistant K. pneumoniae (CRKP) strain showed resistance towards gentamicin (GN). Phages were isolated using double-layer agar method against clinical- and community-acquired K. pneumoniae as host strains. Phage characterization using PCR partial sequencing of different viral genes; Lysin, Major Capsid Protein (g23) and Tail Fiber Protein has suggested that these phages possibly belonged to Myoviridae (ɸKPaV04, ɸKPaV08, ɸKPaV12) and Podoviridae (ɸKPaV03, ɸKPaV10). The characterized phages was selected for cocktail have exhibited high titer and broad host range with 22-44% lysis towards a panel of 18 K. pneumoniae strains. The antimicrobial efficacy of a single phage cocktail administration showed 80% growth suppression of GN-resistant K. pneumoniae after 18 h of incubation. Suggesting the possibility of phage cocktail to be used against nosocomial infections by multidrug resistant bacteria including being an alternative to antibiotic GN in the treatment of CRKP infections.